Angiogenesis in cardiopulmonary dirofilariosis: does the Wolbachia surface protein have a pro- or anti-angiogenic effect?. (2020) - Zueva, T.; Morchón, R.; Carretón, E.; Ollauri-Ibáñez, C.; Pericacho, M.; Rodríguez-Barbero, A.; Simón, F.
Abstract: Cardiopulmonary dirofilariosis caused by Dirofilaria immitis produces inflammation, blood vessel obstruction and hypoxia, which are required conditions for the beginning of the process of neovascularization. Since D. immitis harbours intracellular symbiotic Wolbachia bacterium, the global understanding of the angiogenic process requires the analysis of the effect of the parasite molecules, but also that of Wolbachia . Canine primary lung microvascular endothelial cells were treated with the recombinant Wolbachia surface protein (rWSP) and the expression of angiogenic factors like Vascular Endothelial Growth Factor-A (VEGF-A), sFlt, membrane Endoglin (mEndoglin) and soluble Endoglin (sEndoglin), as well as the in vitro formation of pseudocapillaries, were measured. The analyses showed a significant increase in the expression of pro-angiogenic VEGF-A and anti-angiogenic sEndoglin, together with a significant decrease in both pro-angiogenic mEndoglin and pseudocapillary formation, compared to untreated controls. Due to the complexity of the angiogenic process and its relationship with other physiological processes like inflammation and fibrinolysis, these results might suggest that rWSP participate in various mechanisms related to each other and its effects might depend either on the balance between them or on the moment of their occurrence.